Analisis “Bab IV Satu Titik” Buku Siswa Kelas 4 SD Berdasarkan Kelayakan Buku BSNP Berbantuan EYD Edisi V - Darwoto, Devianti Revalia Wijaya; Purwati, Panca Dewi; Putra, Hafied Ardy; Zaharoh, Sofiatul; Najwatin, Binta Safira; Saputri, Tia Aprilliana (Universitas Negeri Padang, 2025)
The purpose of this study is to analyze the feasibility of content, language, presentation, and graphography in Chapter 6